Management of the Implementation of the Ali Method in Improving the Quality of Tahsin Al-Qur'an Learning - Khalidah, Fatiya Al; Rubini (El-Idare: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the management of the implementation of the 'Ali Method in improving the quality of learning tahsin Al-Qur'an at SDITQ Al Kautsar Sepatan Timur, Tangerang Regency. The background of this research is based on the low ability of students to read the Qur'an and the importance of systematic learning management from the perspective of Islamic education management. The research uses a qualitative approach with a case study type. Data collection techniques are carried out through observation, interviews, and documentation involving school principals, teachers, students, and parents. Data analysis is carried out through data reduction, data presentation, and conclusion drawing with triangulation techniques to maintain data validity. The results of the study show that the implementation of the 'Ali Method has been quite effective through the application of education management functions which include planning, implementation, evaluation, and supervision. Learning is carried out in a structured manner through the 3T approach (Talqin, Tarkiz, Tahqiq) and a leveling system that is able to improve the quality of students' reading of the Qur'an. This method has the advantage of using code, movement, and hands-on learning that makes it easier for students to understand. However, there are still several obstacles, such as not optimal learning differentiation, variations in teacher competencies, and evaluation and supervision systems that are not fully data-based. This research makes a theoretical contribution to the development of Islamic education management studies, especially on tahsin learning management, as well as practical implications for educational institutions in managing Qur'an learning more effectively, systematically, and sustainably.